نقد التصور السوسيولوجي للقيم الاجتماعية - لوحيدي, فوزي (جامعة الوادي - University of Eloued, 2021)
سنحاول في هذا المقالة أن نقدم تعريفا للقيم الاجتماعية ونتعرف على علاقتها مع المفاهيم المقاربة ، كما سنحاول أن نتطرق الى مجهودات السوسيولوجيين وإسهاماتهم في إثراء موضوع القيم ، وذلك من خلال الاستقصاء على طريقتين ، الأولى تعتمد على طرح رأي الاتجاهين البارزين في علم الاجتماع ، والطريقة الثانية هي محاولة تتبع أراء بعض العلماء على حدى ،ثم حاولنا تقديم نقد لإسهامات السوسيولوجيين في دراسة القيم ، لنختم الدراسة بخاتمة تحوصل الموضوع . Abstract In this article, we will try to présent a presentation that provides a definition of social values and learn about their relationship with approaching concepts. We will also try to address the efforts of sociologists and their contributions to enrich the issue of values, through two methods of investigation. The first is to present an opinion that makes prominent people in sociology, and the second method is an attempt. Evaluate the evaluation of the study with a conclusion reached the topic.
A critique of the sociological perception of social values
مقال
Keywords: القيم، القيم الاجتماعية ، علماء الاجتماع; values, social values ,sociologists